2012
DOI: 10.19030/iber.v11i11.7407
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Basel III On Italian Banks Loan Rates: An Accounting-Based Approach

Abstract: This paper empirically investigates the impact of the new capital requirements imposed under Basel III on bank lending rates.A general accounting equilibrium model is developed in order to map the change in the average interest rate on bank loans which is required to preserve the economic performance and the market value of financial institutions under the new regulatory framework.The study refers to the Italian banking system. According to our estimates, the long-term impact of heightened capital requirements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Di Biase (2012) evaluates the impact of increasing minimum capital requirements on the Italian banking industry. He finds that increased capital standards boost a bank's ROE when lending rates rise.…”
Section: Literature On Basel Regulationmentioning
confidence: 99%
“…Di Biase (2012) evaluates the impact of increasing minimum capital requirements on the Italian banking industry. He finds that increased capital standards boost a bank's ROE when lending rates rise.…”
Section: Literature On Basel Regulationmentioning
confidence: 99%
“…Parcon et al (2012) argue that an increase in lending rates, as a strategy to meet the new capital requirements may have a negative impact on the economy. In some countries, it was found that the implementation of higher CAR impacts positively on LSR (Wong, 2010;Di Biase, 2012), while in other countries the higher CAR has a neutral impact on LSR as a result of Basel III implementation. Using an accounting-based model, King (2010) has estimated how much LSR would increase if banks are required to hold more capital.…”
Section: Relation Between Capital Adequacy and Lending Spread Ratiosmentioning
confidence: 99%
“… 39 Anagnostopoulos and Kabeega, 2019; Andrle et al, 2019; Avadanei, 2013; Daniels, 2017; di Biase, 2012; Klepczarek, 2015; Lavelle, 2019; Price, 2016; Quaglia, 2019; Véron, 2020; Young, 2014.…”
mentioning
confidence: 99%
“… 42 Boora, 2018; Cummings and Guo, 2020; Denk and Gomes, 2017; di Biase, 2012; Golubeva et al, 2019; Grundke and Kühn, 2020; Jasrotia et al, 2019.…”
mentioning
confidence: 99%